Impact Of Packaging As A Marketing Tool On Consumer Purchase Intention - Samimi, Soroush (2011)
The research utilized a survey methodology to understand consumer purchase behavior toward such products and how packaging elements can affect buying decisions or better to say consumer purchase intention. Extrinsic package elements play a vital role in representing the product for many consumers, especially for low involvement consumers when they are in hurry to buy their goods.